PROBLEMATIKA IZIN PENYADAPAN OLEH DEWAN PENGAWAS DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI - Nazahra Zea Syakina (2022)
To combat corruption, the Corruption Eradication Commission has extraordinary authority to wiretap someone named in a corruption investigation. Wiretapping is a strong tool for uncovering a unique crime. Wiretapping rules are still strewn throughout many statutes, with differing implementation measures. The KPK has established a supervisory body known as the Supervisory Board as part of the legislative reform. The creation of the KPK supervisory board has sparked debate regarding its powers and responsibilities in overseeing the KPK. The Supervisory Board's authority has been renewed with the decision to seek judicial review of the new articles in the KPK Law amendment. The goal of this study was to see how the wiretapping mechanism worked in eradicating corruption and the Supervisory Board's authority after the Constitutional Court's ruling number. 70/PUU-XVII/2019. Through a linked legislation approach and a conceptual approach, the study method adopted is normative juridical. The literature review method was used to acquire data for this investigation. According to the findings of the study, the process of wiretapping in the fight against corruption is not well-defined under the KPK Law. Furthermore, the supervisory board's jurisdiction to grant prior authorisation to undertake wiretapping, searches, and seizures is deemed unlawful. Because the supervisory board is not a law enforcement officer, granting pro justicia authority to the board is deemed an act of intervention. As a result, the supervisory board's wiretapping authority is limited to obtaining information about wiretapping actions.